Raman Spectroscopy for the Competition of Hydrogen Bonds in Ternary (H2O–THF–DMSO) Aqueous Solutions - Shiliang Liu (Molecules, 2019)
The effects of hydrogen bonds on the molecular structure of water-tetrahydrofuran (H2O−THF), water-dimethyl sulfoxide (H2O−DMSO), and water-tetrahydrofuran-dimethyl sulfoxide (H2O−THF−DMSO) in binary aqueous solutions and ternary aqueous solutions were studied using Raman spectroscopy. The results indicate that in the binary aqueous solution, the addition of THF and DMSO will generate hydrogen bonds with water molecules, resulting in changes in the peak positions of S=O bonds and C−O bonds. Compared with the binary aqueous solutions, the hydrogen bonds between DMSO and THF, and the hydrogen bonds between DMSO and H2O in the ternary aqueous solutions are competitive, and the hydrogen bond competition is susceptible to water content. In addition, the formation of hydrogen bonds will destroy the fully hydrogen-bonded water and make it change to the partially hydrogen-bonded water. By fitting the spectra into the three Gaussian components assigned to water molecules with different hydrogen bonding (HB) environments, these spectral features are interpreted by a mechanism that H2O in different solution systems has equal types of water molecules with similar HB degrees-fully hydrogen-bonded H2O (FHW) and partially hydrogen-bonded H2O (PHW). The ratio of the intensity transition from FHW to PHW is determined based on Gaussian fitting. Therefore, the variation of hydrogen bond competition can be supplemented by the intensity ratio of PHW/FHW ((IC2 + IC3)/IC1). This study provides an experimental basis for enriching the hydrogen bonding theory of multivariate aqueous solution systems.